Production of Phophatase by mutated fungal strains - Ilyas*, Jayaraman Rajeshkumar; M.H. Muhammad (International Multidisciplinary Research Journal, 2011)
Phosphate solubilizing microorganisms were isolated from rhizosphere soils of rice fields around Mannachanalur area, Tiruchirappali district of Tamilnadu. The isolated fungal cultures were identified as Aspergillus niger, Aspergillus fumigatus and Penicillium sp. The efficacy of Phosphatase activity of fungal strains was carried out. The fungal strains were subjected to random mutational studies such as UV and chemical mutation. The Phosphatase assay was carried out after random mutagenesis using wild and mutated cultures. The efficacy of Phosphatase activity of the wild strains were observed in the descending order of Aspergillus niger > Penicillium sp. > Aspergillus fumigatus. Among the chemical treated fungal strains, Aspergillus niger (ANsa120) was the predominant fungal strain for Phosphatase activity. Glucose and Ammonium sulphate were found to be the best carbon and nitrogen source respectively for both phosphate solubilization and phosphatase production. Significance of the findings is discussed in detail.